Molecular spectroscopy characterization of binary liquid mixtures using attenuated total reflectance-fourier transforms infrared approach. - Mohammed Rashid, Ali; Abdulla, Firdos M.; Noor Asma Fazli, Abdul Samad (IJAR, 2019)
The spectrometry properties are important in understanding the molecular interaction between unlike molecules in binary liquid mixtures. The spectrometry characterizations of individual components and binary mixtures of MTBE, methanol, DIPE and NMA were succinctly investigated in this study. The interaction between MTBE and other components such as DIPE, methanol and NMA can be observed mainly through interaction between the C-O-C groups of MTBE and the functional groups of the other components. These interactions can either be through the hydrogen bonding or the formation of complexes. As such, some of the functional groups of interest in the components studied herein include C-O-C, -OH, C-H, C-O and N-H groups. All these indicate that intermolecular interaction between MTBE and methanol is more evident in the binary mixture containing 70 % MTBE and 30 % methanol, compared to the binary mixture containing 30 % MTBE + 70 % methanol. Moreover, the results of the interaction between MTBE and DIPE indicated that there is no intermolecular interaction between them. However, the interaction between MTBE and NMA showed that most of these peaks are slightly shifted in the spectrum of the binary mixture containing 70 % MTBE and 30 % which indicated a more effective molecular interaction between MTBE and NMA are more effective at higher MTBE content rather than lower MTBE content.